Research trends of flipped classroom studies for medical courses: a review of journal publications from 2008 to 2017 based on the technology-enhanced learning model. Issue 8 (17th November 2019) - Lin, Hui-Chen; Hwang, Gwo-Jen
ABSTRACT: Medical education is a domain with fast-changing knowledge and attention to knowledge application and higher order thinking; therefore, how to implement effective teaching is a crucial issue. Based on the technology-based learning model, this study provides a multi-dimensional analysis of published papers on the flipped classroom in medical education from the SCOPUS database, including the form of the learning materials, learning system or player, learning strategies, educational technology, application domains, research issues, participants, and research methods. Based on the results, the application of flipped classrooms in medical education has grown rapidly over the past decade, with the number growing dramatically from 7 papers in 2014, to 16 papers in 2015, and 22 papers in 2016. It was found that a great number of studies adopted instructional videos uploaded on online learning systems or used existing online videos to conduct before-class teaching in the before-class stage of the flipped classroom; moreover, most studies involved no online discussion in the before-class stage. As for learning strategies in the in-class stage, the most frequently adopted strategies were issue discussion, practicing or doing exercises, and problem-based learning. This implies that most studies mainly emphasized basic knowledge understanding and skills training, while little attention was paid to developing learners' higher order thinking skills. In addition, the majority of studies explored students' learning interest/satisfaction, learning experience, and performance on the cognitive aspect, while little research was found to investigate their preparation degree or cognitive loading. Based on the review results, this study provides the research trends and potential research issues of flipped medical education to serve as a reference for researchers, instructors, and decision makers.